Implementasi Program Beasiswa Melalui Ruangguru Corporate Social Responsibility (CSR) PT Wijaya Karya Beton TBK - Vivin Herial; Siti Chairunissa Yazahira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the implementation of the CSR program carried out by PT Wijaya Karya Beton Tbk, reviewed from the perspectives of motives, forms, or models of CSR implementation. A qualitative approach was used, with data collection techniques through interviews and observations, which revealed that the company's motive for implementing the CSR program is based on political theories. Furthermore, various forms, models, and characteristics explain how a company implements its CSR program. Based on the program model, PT Wijaya Karya Beton Tbk integrates different CSR distribution models in its implementation, including direct involvement in activities, channeling CSR through social institutions or independent foundations, partnering with other institutions or foundations, or providing support and participating in an activity. Moreover, when viewed from the three forms of CSR implementation, PT Wijaya Karya Beton Tbk's CSR program is implemented in two forms: community relations, carried out through a scholarship program in partnership with the educational institution Ruangguru, and community empowerment, which is also part of the scholarship program in collaboration with Ruangguru stakeholders. The aim of this CSR implementation is to empower communities to achieve a level of citizenship that enhances their competitiveness.